Moderasi Beragama Di Indonesia Dalam Perspektif Fiqih Pemikiran Yusuf Al Qardhawi - Al-Hasyimi, Muhammad Luthvi; Nisa, Khoirun (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
he purpose of conducting this research is so that as a Muslim who lives in a country with various ethnicities, races and religions, he can determine the correct attitude according to Islamic law according to the Koran and al-Hadith. The researcher used a qualitative research type of library study using various relevant scientific reference sources and then documented it using a normative, philosophical approach. The results of this research are that a Muslim needs to have an attitude of religious moderation in state life without having to compromise his religious beliefs, apart from that it is clearly stated in the Koran that as a Muslim it is forbidden for him to insult the deities of other religions according to Yusuf Al-Qaradawi's thoughts.